Economic reforms and development in Vietnam (Social Science Pub. House, 1995)
This book introduce about economic reforms and cocio-economic problems of development. Economic reforms and changes of economic structure in development process. Economic reforms and poverty alleviation in rural areas. Economic reforms and gender issues.